O FINANCIAMENTO À PESQUISA E PÓS-GRADUAÇÃO NA UFF: UM ESTUDO DE CASO - Faria, Maria Leonor Veiga (2005)
The current policy of governmental financing for the Universities can be verified in the global prices placed by the Government for expenses of Other Costs and Capital OCC, which have not been enough for the necessary maintenance and investment to the development and expansion of the Brazilian Universities, making them search for resources out of their bridget in a way to complement the ones that come from MEC. The present study has as its main purpose to examine and explicit the strategies that are being developed at Universidade Federal Fluminense in order to develop and expand its post-graduation and research activities facing the new financing policy developed for the sector. News ways of organization, which are bring processed at UFF with the purpose of complementing the bridget came from MEC through the increase in getting external resourses and internal bridget, were observed. It has analyzed the matter of the auto-financing courses in a public institution and what benefits they bring to that institution and it has also analyzed the role of the university management in the increase of the post-graduation research at UFF. Through the results, it has observed the acceptance from the scientific-academic comunity at UFF and other managers, the new implemented activities at PROPP, specially bid for research grant, through its incorporation to the Institutional Development Plan of UFF.